2017
DOI: 10.1080/13607863.2017.1320702
|View full text |Cite
|
Sign up to set email alerts
|

Regional responses to the challenge of delivering integrated care to older people with mental health problems in rural Australia

Abstract: Objective: Integrated care has been identified as means of managing the demands on the healthcare budget while improving access to and quality of services. It is particularly pertinent to rural health services, which face limited access to specialist and support services. This paper explores the capacity of three rural communities in South Australia to deliver integrated mental health support for older people.Methods: Thirty-one interviews were conducted with local health and social service providers from ment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
60
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(61 citation statements)
references
References 22 publications
(38 reference statements)
0
60
0
Order By: Relevance
“…In this study, low financial resources, difficult geographical terrain, and family indifferences towards mental illness compounded and contextualized the challenge of low accessibility of mental healthcare services in rural Mbarara district. Similarly, inadequate patient flow process as identified in this study and others [37,39,40,[44][45][46][47][48][49][50][51] contextually contributed to the poor accessibility of care. When we looked at these findings in relation to the SURE framework, we noted that adequate processes for outreach and receiving, referring and transferring patients is needed to address this constraint in Mbarara district.…”
Section: Discussionmentioning
confidence: 60%
“…In this study, low financial resources, difficult geographical terrain, and family indifferences towards mental illness compounded and contextualized the challenge of low accessibility of mental healthcare services in rural Mbarara district. Similarly, inadequate patient flow process as identified in this study and others [37,39,40,[44][45][46][47][48][49][50][51] contextually contributed to the poor accessibility of care. When we looked at these findings in relation to the SURE framework, we noted that adequate processes for outreach and receiving, referring and transferring patients is needed to address this constraint in Mbarara district.…”
Section: Discussionmentioning
confidence: 60%
“…The connectors in this study provided a safe space for health staff to enter the community milieu, with potential for staff to respond by adapting service characteristics, or their own attitudes and behaviours, to improve access. While our study has shown examples of staff making modest changes to service availability or delivery in response to requests from connectors, the reality is that funding, fragmentation of responsibility and bureaucratisation of services [61] However, supporting the capability of individuals is only part of the process of accessing services, as characteristics of the local health system also impact on accessibility creating generalised institutional rules of engagement that have to be negotiated [61,62]. These play out in the dimensions of accessibility relating to approachability, acceptability and availability [4,9].…”
Section: Discussionmentioning
confidence: 87%
“…The connectors in this study provided a safe space for health staff to enter the community space, with potential for staff to respond by adapting the characteristics of local services to improve access. While our study has shown examples of staff making modest changes to service availability or delivery in response to requests from connectors, the reality is that funding, fragmentation of responsibility and bureaucratisation of services [61] create system boundaries that challenge the ability of local staff to make larger scale changes. Increasing pressure on health budgets, coupled with funding models based on episodes of care results in a reduction of the health promotion and community development resources [61] required for collaborating with connectors.…”
Section: Discussionmentioning
confidence: 90%
“…The connectors in this study did this through facilitating access to health information as well as service navigation or referral. However, supporting the capability of individuals is only part of the process of accessing services, as characteristics of the organisation also impact on accessibility creating generalised institutional rules of engagement that have to be negotiated [60,61]. These play out in the dimensions of accessibility relating to approachability and availability [4,9].…”
Section: Discussionmentioning
confidence: 99%